The impact of the Oracle accounting information system on evaluating the institution’s financial performance and improving the quality of the financial statements - Case study of Algeria Telecom (Central) - - achouri, Badereedine; taibi, Hamza (Journal of Excellence for Economics and Management Research, 2022)
The study aims to research the reality of accounting information systems in Algiers Telecom Corporation - Central - and their impact on the evaluation of financial performance during the period (2016-2018) and highlight their importance in improving financial statements with high quality, reliability, understandable and analysis based on some indicators and ratios of financial analysis to give a picture of the status of the institution. The study concluded that accounting information systems have facilitated accounting practices and improved the quality of financial statements within the institution and provide accurate, high-quality, credible and reliable information, in addition to evaluating the financial performance of the institution, and in order to adopt an effective information system, institutions must adhere to the appropriate principles and standards and give it a frothy of attention to highlight its role in the preparation and improvement of financial statements.